2021
DOI: 10.1177/02654075211041539
|View full text |Cite
|
Sign up to set email alerts
|

Support gaps during the COVID-19 pandemic: Sex differences and effects on well-being

Abstract: During times of stress, supportive communication can buffer individuals from experiencing negative outcomes. However, the COVID-19 pandemic has substantially altered the interactions people rely on for support, which may influence the supportive messages they desire and receive. When people receive quantities of support that differ from what they desire, they experience support gaps, which are often associated with negative outcomes. The present study examines: (a) support gaps in close relationships under she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
(140 reference statements)
1
7
0
Order By: Relevance
“…Black individuals experienced more instrumental social support than white individuals ( Philpot et al, 2021 ). In another study, U.S. college students received more esteem, informational, and tangible support than they desired from their closest relational partners ( Holmstrom et al, 2021 ). Understanding the satisfaction of different groups’ social support needs is fruitful for future research to better serve groups with preexisting contextual vulnerabilities and those managing enduring individual vulnerabilities ( Pietromonaco & Overall, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Black individuals experienced more instrumental social support than white individuals ( Philpot et al, 2021 ). In another study, U.S. college students received more esteem, informational, and tangible support than they desired from their closest relational partners ( Holmstrom et al, 2021 ). Understanding the satisfaction of different groups’ social support needs is fruitful for future research to better serve groups with preexisting contextual vulnerabilities and those managing enduring individual vulnerabilities ( Pietromonaco & Overall, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…In a U.S. sample, social support from family, friends, and a specific loved one were each associated with increased resilience during early lockdown ( Killgore et al, 2020 ). Having less emotional support than desired from one’s closest relational partner predicted decreased relational satisfaction, while more esteem support than desired increased both satisfaction and stress ( Holmstrom et al, 2021 ). Again, this pattern of findings supports the link between social support as an adaptive dyadic relationship process that contributes to increased relationship stability in the face of an external stressor like COVID-19 proposed by Pietromonaco and Overall’s (2021) adapted VSA model.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…One interpretation of these findings is that receiving greater amounts of support than desired in the face of severe, prolonged stressors like a global pandemic is more beneficial for fostering resilience than receiving a lesser, yet matched amount of support. A recent study on support gaps during the COVID‐19 pandemic revealed similar findings, with surpluses in support contributing to enhanced well‐being, lower levels of perceived stress, and greater relational satisfaction (Holmstrom et al, 2021). Furthermore, surpluses in esteem support (Holmstrom et al, 2021) and identity support (Davis & High, 2019) have been associated with affect improvement and reduced perceptions of stress.…”
Section: Discussionmentioning
confidence: 73%
“…Accordingly, support is theorized to be critical in sustaining relationship quality during the pandemic ( Pietromonaco & Overall, 2021 ) and has been a key focus of pandemic-related research. Initial studies show that perceived partner support predicted better psychological health and couple and parenting outcomes during the early months of the pandemic ( Brown et al, 2020 ; Donato et al, 2021 ; Holmstrom et al, 2021 ; McRae et al, 2021 ; Ogan et al, 2021 ; Randall et al, 2021 ). We extend these findings by testing whether partner support helped sustain parents’ health and functioning across the first 1.5 years of the pandemic (from Lockdown 2020 to 2021).…”
Section: Moderators Of Risk Versus Resiliencementioning
confidence: 99%